Training on Strengthening Fishery Business Groups in Development In Lambusa Village, Konda District, South Konawe Regency - Arsyad, Muhammad; Suaib, Eka; Hos, Jamaluddin; Yusuf, Bakri; Bahtiar; Peribadi; Supiyah, Ratna; Roslan, Suharty; Sarpin; Ridwan, Harnina (CV. Literasi Indonesia, 2024)
The Training on Strengthening Fishery Business Groups in Lambusa Village, Konda District, South Konawe Regency, succeeded in improving the skills and knowledge of villagers in the cultivation, processing, and marketing of fishery products. Participatory training methods involving counseling and practice have proven to be effective in building internal group relationships as well as connectivity with governments, financial institutions, and market participants. The training includes fishery resource management, sustainable aquaculture techniques, marketing, and financial management, which supports increasing the productivity and income of fishery business groups. As a result, there has been an increase in solidarity and cooperation between members, as well as village social and economic welfare. The training also strengthens the concept of community empowerment through a participatory and sustainable approach, providing applicative skills to overcome concrete problems and achieve self-reliance. The evaluation showed the high enthusiasm of the participants and the significant application of knowledge, contributing to the sustainable development of the village and the capacity building of the fishery business group.